1987
DOI: 10.1038/bjc.1987.119
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cell-free interleukin 2 receptor level in the serum of normal animals and of animals bearing IL-2 receptor positive tumours with high or low metastatic capacity

Abstract: Summary Serum levels of cell-free interleukin-2 receptors were elevated above normal in mice bearing the IL-2R positive T-cell lymphoma Eb or its highly metastatic variant ESb. Although ESb cells expressed less IL-2R molecules than Eb cells on their cell surface, serum receptor levels were raised more quickly in ESb than in Eb tumour bearing animals. Elevated IL-2R serum levels were a sensitive tumour marker in animals bearing the aggressive variant ESb but not in animals bearing the low metastatic line Eb. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…6 These cellular responses are mediated by a surface receptor complex of which three separate peptide chains have been described.7 1718 The et chain of the receptor (Tac protein) is released from the cell surface8 and in its soluble form retains affinity for interleukin 2.19 The rate of release is related to the degree of surface expression (T cell activation). Soluble interleukin 2 receptor concentration is raised in diseases such as graft versus host disease,20 rapidly progressive scleroderma or systemic lupus erythematosus,2' lymphoreticular malignancy, 22 and systemic but not localised parasitic infection.23 An excellent correlation exists between serum soluble interleukin 2 receptor concentration and the Ritchie articular index in rheumatoid arthritis, in which falls in receptor concentration predict clinical improvement and rises are seen before clinical relapse. '0 We found that on admission to hospital patients with atopic eczema had higher concentrations of serum soluble interleukin 2 receptor than controls matched for age.…”
Section: Discussionmentioning
confidence: 99%
“…6 These cellular responses are mediated by a surface receptor complex of which three separate peptide chains have been described.7 1718 The et chain of the receptor (Tac protein) is released from the cell surface8 and in its soluble form retains affinity for interleukin 2.19 The rate of release is related to the degree of surface expression (T cell activation). Soluble interleukin 2 receptor concentration is raised in diseases such as graft versus host disease,20 rapidly progressive scleroderma or systemic lupus erythematosus,2' lymphoreticular malignancy, 22 and systemic but not localised parasitic infection.23 An excellent correlation exists between serum soluble interleukin 2 receptor concentration and the Ritchie articular index in rheumatoid arthritis, in which falls in receptor concentration predict clinical improvement and rises are seen before clinical relapse. '0 We found that on admission to hospital patients with atopic eczema had higher concentrations of serum soluble interleukin 2 receptor than controls matched for age.…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve was prepared by plotting the absorbance of the sIL-2R standard versus the corresponding concentration, and the concentration of sIL-2R in unknown sera determined by interpolation from this standard curve. This assay has a detection range from 20 to 1600 U ml -1 with an intra-assay coefficient of variation (CV) of around 2.5% [11].…”
Section: Quantification Of Sil-2rmentioning
confidence: 99%
“…7 1718 The et chain of the receptor (Tac protein) is released from the cell surface8 and in its soluble form retains affinity for interleukin 2.19 The rate of release is related to the degree of surface expression (T cell activation). Soluble interleukin 2 receptor concentration is raised in diseases such as graft versus host disease,20 rapidly progressive scleroderma or systemic lupus erythematosus,2' lymphoreticular malignancy, 22 and systemic but not localised parasitic infection.23 An excellent correlation exists between serum soluble interleukin 2 receptor concentration and the Ritchie articular index in rheumatoid arthritis, in which falls in receptor concentration predict clinical improvement and rises are seen before clinical relapse. '0 We found that on admission to hospital patients with atopic eczema had higher concentrations of serum soluble interleukin 2 receptor than controls matched for age.…”
mentioning
confidence: 99%